Global Justice’s Critics of Green Politics Theory Towards International Rules of Climate Change - Tri Utami, Arum (UIN ALAUDDIN MAKASSAR, 2023)
Environmental issues have become a concern issues in the last decades. Green Politics emerge as an enforcement from the global community because of the climate change problem in the world. Green Politics emphasized on the decentralization of power to solved the environmental issues. The role of individual become important in solving environmental issues. If each individual has the similar awareness,it could be solved the environmental issues. Global Justice come up and claimed as a solution to see the environmental problems. According to global justice, the equal right in opportunities is the key of handling the climate change. States is an actor that can facilitated the movement of climate change. The perception of global justice perceive if individual is the main actor in environmental issues, it would not be unfair to individual in the developing countries. Distributive of justice is needed to make developing countries have a similar opportunities to reach a similar improvement liked developed countries.